Adsorbent pad selection for colorimetric biosensor of hydration imbalance - Goh, Chee Hong (2015)
Dehydration and over-hydration are common during durable sport activities which would lead to hydration problem such as muscle cramps, nausea, or even death. However, a portable and user-friendly colorimetric biosensor to monitor individual hydration status has not been developed in this market and they emphasize the need of real-time biosensors which benefit the people participating in durable sports. Unique optical properties of gold nanoparticles give the idea of this project to monitor hydration status. As concentration of sodium ions in sweat increases, the gold nanoparticles would aggregate and exhibit different colors in response to visible light range which could be observed by naked eye. Three distinct colors have been achieved by the previous two project collaborators to distinguish individual from dehydration, euhydration and over-hydration. The prototype development is further conducted by choosing the suitable adsorbent pad to store the gold nanoparticle and induce color change by different hydration situations (different concentrations of NaCl) in order to make the final product to be user-friendly. Nonetheless, only Cellulose Extraction Thimbles able to show slight color change of the gold nanoparticles from dark purple to light purple. This study is recommended to investigate more candidates of adsorbent pads in future. Besides, it is encouraged to construct a standard light box to standardize the conditions of photo taking and software such as Adobe Photoshop could be used to justify the color change quantitatively.